Design and optimization of co-production process of natural gas liquefaction and BOG helium extraction - Rongge XIAO; Linnan PANG; Yalong LIU (You-qi chuyun)
Natural gas liquefaction requires massive cold energy, but the single liquefaction process can not fully utilize the cold energy, so that much of it is wasted. Besides, storing LNG generates a large amount of BOG that demands urgent care in order to prevent production accidents. Therefore, for the purpose of energy saving, consumption reduction and full utilization of the cold energy, this study proposes an innovative co-production process combining nitrogen cyclic expansion refrigeration based natural gas liquefaction and BOG cryogenic helium extraction, This study uses the HYSYS software to simulate the nitrogen cyclic expansion refrigeration based natural gas liquefaction, the BOG cryogenic helium extraction and the co-production process, and analyzes the key parameters relating to the comprehensive energy consumption and the crude helium concentration. While maintaining the crude helium concentration at 76.8%, the co-production system, with the goal of minimizing the comprehensive energy consumption, was optimized by applying the response surface method and the genetic algorithm into the process. The optimal parameters obtained were as follows: the high pressure of the refrigerant was 7 005 kPa while the low pressure was 489 kPa and the flow rate was 4 000 kmol/h. The feed temperature and the feed pressure of the cryogenic were -130 ℃ and 2 390 kPa respectively. In the co-production process, the natural gas liquefaction rate exceeded 90%, the helium recovery rate exceeded 95%, and the crude helium volume fraction exceeded 76.8%. Compared with the single liquefaction process, the total compression power consumption in the co-production process was reduced by about 23.6%, 4 022.71 kW in number; and the overall energy consumption was reduced by about 18.00%, 3 482.4 kW in number. The simulation results suggest that the co-production process is more cost-effective and energy-efficient. This study could provide a reference for the engineering application of the newly designed co-production process.